Pengaruh Sikap Keuangan, Literasi Keuangan, dan Gaya Hidup Hedonisme Terhadap Manajemen Keuangan (Studi Kasus UMKM di Kecamatan Banjaran Kabupaten Bandung) - Huda Fitrianti; Devyanthi Syarif (IKRAITH-EKONOMIKA, 2025)
This study aims to analyze the influence of financial attitudes, financial literacy, and hedonistic lifestyles on the financial management of MSME actors in Banjaran District, Bandung Regency. The background of this study is the weak financial management of MSMEs due to social pressures in the digital era that trigger consumptive behavior. The study used a quantitative approach with a causal design on 100 MSME actors selected through accidental sampling (Slovin formula). Data were collected using a 5-point Likert scale questionnaire and analyzed using multiple linear regression. The results showed that: (1) financial attitude had a significant positive effect on financial management (t=4.111; p=0.000), (2) financial literacy has a significant positive effect with the most dominant influence (t=5.087; p=0.000), (3) hedonistic lifestyle has a significant negative effect (t=-2.815; p=0.006). Simultaneously, the three variables have a significant effect (F=36.978; p=0.000) with a 53.6% contribution to the financial management of MSME actors. The practical implications of this study emphasize the importance of improving financial literacy, forming positive financial attitudes, and controlling hedonistic behavior as the keys to successful MSME financial management.